The impact of the social environment on youth social adaptation in the digital era - Alex R I Ompusunggu (Interaction, Community Engagement, and Social Environment, 2026)
Background: The rapid evolution of digital technology has significantly shaped the social environment and altered the ways youth interact, communicate, and adapt within society. This study aims to analyze how social environments both offline and online affect youth social adaptation in the digital era, emphasizing sociocultural and psychological dimensions. Prior research indicates that digitalization encourages broader connectivity but can simultaneously reduce empathy and direct interpersonal communication. Methods: This study employs a literature review method, systematically synthesizing peer-reviewed journal articles and theoretical studies from the past decade. The analysis applies social ecology and adaptation theory to explore the interrelationship between environmental influences and adaptive behaviors among youth. Findings: Findings reveal that supportive social environments enhance digital literacy, emotional resilience, and social inclusion among young people, while toxic online cultures and social pressures contribute to isolation and maladaptive behaviors. The theoretical synthesis shows a reciprocal influence between environmental context and adaptive capacity highlighting that digital participation must be balanced with real world social skills to achieve well rounded adaptation. Conclusion: A balanced and inclusive social environment remains crucial for promoting adaptive social development among youth in a digitally interconnected society. Novelty/Originality of this article: The novelty of this article lies in its integrative theoretical approach, combining social ecology and adaptation perspectives to reinterpret youth social adaptability within the context of digital transformation.